Degradation of Acid Blue 40 dye solution and dye house wastewater from textile industry by photo-assisted electrochemical process - Moraes, Peterson B.; Pelegrino, Rosangela R. L.; Bertazzoli, Rodnei (Taylor & Francis Inc, 2007)
In this paper, electrochemical and photo-assisted electrochemical processes are used for color, total organic carbon (TOC) and chemical oxygen demand (COD) degradation of one of the most abundant and strongly colored industrial wastewaters, which results from the dyeing of fibers and fabrics in the textile industry. The experiments were carried out in an 18L pilot-scale tubular low reactor with 70% TiO2/30% RuO2 DSA. A synthetic acid blue 40 solution and real dye house wastewater, containing the same dye, were used for the experiments. By using current density of 80 mA cm(-2) electrochemical process has the capability to remove 80% of color, 46% of TOC and 69% of COD. When used the photochemical process with 4.6 mW cm(-2) of 254nm UV-C radiation to assist the electrolysis, has been obtained 90% of color, 64% of TOC and 60% of COD removal in 90 minutes of processing; furthermore, 70% of initial color was degraded within the first 15 minutes. Experimental runs using dye house wastewater resulted in 78% of color, 26% of TOC and 49% of COD in electrolysis at 80 mA cm(-2) and 90 min; additionally, when photo-assisted, electrolysis resulted in removals of 85% of color, 42% of TOC and 58% of COD. For the operational conditions used in this study, color, TOC and COD showed pseudo-first-order decaying profiles. Apparent rate constants for degradation of TOC and COD were improved by one order of magnitude when the photo-electrochemical process was used.
Keywords: electrochemical treatment; DSA electrodes; textile dye degradation; acid blue 40; photo-electrochemical process